Open Data and Models for Energy and Environment - Nastasi, Benedetto; Manfren, Massimiliano; Noussan, Michel (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This Special Issue aims at providing recent advancements on open data and models. Energy and environment are the fields of application.For all the aforementioned reasons, we encourage researchers and professionals to share their original works. Topics of primary interest include, but are not limited to:Open data and models for energy sustainability;Open data science and environment applications;Open science and open governance for Sustainable Development Goals;Key performance indicators of data-aware energy modelling, planning and policy;Energy, water and sustainability database for building, district and regional systems; andBest practices and case studies.